Characterization of local isolates of chickpea symbiotic bacteria grown in AS- Swaida governorate and evaluation of their efficiency in atmospheric Nitrogen Fixation (Journal of Hama University, 2020)
The aim of this study was: Isolate Rhizobia from the chickpea plant, determine its biochemical characters and evaluate its efficiency in fixing atmospheric nitrogen. The research was carried out in the laboratory of bacterial plant diseases in the Faculty of Agriculture-Damascus and in the glass house of the National Commission of Biotechnology for the agricultural season 2017 2018. Plant samples were collected from different locations of AS-Swaida governorate, Syria. 120 bacterial strains were isolated, the result of artificial infection showed that 46 isolates formed root nodes. The biochemical tests showed that they belong to the family of Rizobia, Where They was Gram negative, Do not form spores, catalase positive, oxidase negative, able to use some sugars such as xylose, maltose, fructose, galactose, sucrose and mannitol as the source of carbon. they also metabolizes glucose and they are unable to metabolize lactose. some isolates decompose starch and others dissolve gelatin. Estimating the total nitrogen in the plant using Kaldahl method showed that there were significant differences in the quantity of fixing nitrogen between bacterial and non bacterial treated plants. The total nitrogen content in the control was 0.01 g / plant. While the plants were inoculated Bacteria are higher than the value of the control. On the other hand,  There were also significant differences among isolates in their ability to fix the atmospheric nitrogen, whereas The amount of nitrogen was ranged between 0.055 – 0.011  g / plant for isolates  r10.2 from Shahba - Al Ojailat and r 27.2.2 from Shahba – Ezran  respectively.